Early Marriage and Human Development Index in Indonesia - Bayu Kharisma; Adhitya Wardhana; Mohammad Zidan Fauzy (Universitas Udayana, 2024)
Early marriage is a violation of children's rights and can have significant negative impacts. Some of thenegative impacts of early marriage include physical and mental health risks, barriers to achieving goodhuman resources, and increased risk of maternal and child mortality. This study aims to analyze thedeterminants of early marriage on the Human Development Index (HDI) using the GeographicallyWeighted Regression (GWR) method. The estimation results show a significant negative relationshipbetween early marriage and the Human Development Index (HDI), as well as a significant relationshipbetween almost all factors affecting early marriage and HDI, except GRDP per capita, contraceptive use,housing ownership, and child abuse cases. In order to improve human resources and community welfare,the main focus needs to be improving access to education, protecting children's rights, reproductivehealth, and poverty reduction. Preventing early marriage is key to providing optimal opportunities forchildren to grow and develop and promoting higher human development.